Nursing management of allergic dermatitis after peripherally inserted central catheter placement in a patient with Hodgkin's lymphoma (1例霍奇金淋巴瘤患者PICC置管后并发过敏性皮炎的护理) - LI Zhiqun (李志群) (中西医结合护理, 2023)
This paper summarized the nursing management of allergic dermatitis after peripherally inserted central catheter placement in a patient with Hodgkin's lymphoma. Key points of nursing included catheter maintenance, risk assessment, self-management, health education and extended nursing. Individualized nursing interventions were carried out to improve the healing of skin damage. (本文总结1例霍奇金淋巴瘤PICC置管后并发过敏性皮炎患者的护理经验, 包括标准化的导管维护、风险评估管理、患者导管自我管理、带管期间健康宣教、延续性护理等, 通过个性化护理措施, 有效促进患者皮损愈合。)